Aplikasi Pelaporan Data Siswa Berbasis Web (Studi Kasus : SDN Telukan 02 Sukoharjo) - Etika, Rahmawati Nur; , Azizah Fatmawati, S.T., M.Cs (2017)
An information system is helpful to facilitate that work that was previously only done in a simple way can become more efficient. Data management on SDN Telukan 02 Sukoharjo which includes student and teacher data storage and information of student age is still done simply where data is only stored in a data excel. It is less effective in time and effort. Therefore, the application system is essential to the students and teachers data management become more efficient. Student data reporting application is a web-based system designed for the purpose of data management students and teachers that includes the name, address, place and date of birth and age of student reports and other information. Web-based application systems become one of the solutions that aim to solve the problem data management of students and teachers at SDN Telukan 02 Sukoharjo. The method used in the development of students data reporting applications at SDN Telukan 02 Sukoharjo is waterfall method which consist of application planning, application analysis, application design, application implementation and application testing. While, the tools used in development of applications, among others Notepad++, Dreamweaver, phpMyAdmin, Xampp and Mozilla Firefox. The result of the research management and data reporting is web-based application that can be publicly accessed and the administrator as data manager. The testing was done by blackbox method and questionnaire distribution for teachers as the application users. The testing result by blackbox method showed that application is running well with the available features, while from the questionnaire result showed application is useful for managing students and teachers data.